Investigating the role of gender in teacher-student communication and classroom dynamics - Jony, Md. Solaiman (Papanda Publisher, 2025)
Active class involvement has been connected with student engagement and can be a significant aspect of a good learning experience in classrooms. Several aspects influence student engagement including classroom dynamics such as classroom connection, instructor-student relationship and gender of the teacher and student. This paper looks at how teacher gender affects student views, communication patterns, and classroom dynamics in mixed-gender education environments. Specifically, it investigates how a teacher's gender affects students' views of the teacher-student relationship, the communication techniques used in the classroom, and the influence of gender stereotypes on teacher-student interactions and involvement. Using a mixed-methods approach, the study integrates questionnaires, classroom observations, and interviews with students and teachers to acquire insights into these dynamics. A total of 100 students and 10 teachers from secondary level, by maintaining equal gender ratio, were involved in the study. Preliminary data imply that instructor gender plays a substantial influence in setting student expectations, communication effectiveness, and engagement levels, sometimes mediated by societal gender norms and prejudices. Findings reveal that students commonly regard female teachers as more loving and approachable, establishing greater emotional ties, while male teachers are more frequently linked with authority and discipline. Teacher gender also affects communication techniques; female teachers usually use more inclusive and cooperative conversation while male teachers usually use a more directive style. The study emphasizes the need for greater awareness of gendered perspectives in education to build more equal and inclusive learning settings.